Depression, anxiety, stress, and physical activity of Australian adults during COVID-19: A combined longitudinal and repeated cross-sectional study - Zhao, Wei; Vandelanotte, Corneel; Khalesi, Saman; Alley, Stephanie J.; Williams, Sue L.; Thwaite, Tanya L.; Fenning, Andrew S.; Stanton, Robert; To, Quyen G. (Frontiers in Psychology, 2022)
Background: The COVID-19 pandemic has led to a worsening of mental health and health behaviours. While physical activity is positively associated mental health, there is limited understanding of how mental health and physical activity evolve throughout the COVID-19 pandemic. This study aimed to examine changes in depression, anxiety and stress and physical activity, and associations between depression, anxiety and stress with physical activity in Australian adults across three-time points during the COVID-19 pandemic. Methods: This study collected both longitudinal and cross-sectional data at three-time points during the COVID-19 pandemic in Australia (i.e., April, July/August, and December 2020). Australians aged 18 years and over were invited to complete online surveys hosted on Qualtrics survey platform. Linear mixed models with random subject effect and general linear models were used to analyse the longitudinal and repeated cross-sectional data respectively. Results: The number of participants in cross-sectional surveys and longitudinal surveys was 1877 and 849 respectively. There was an overall reduction between time 2 vs. time 3 in depression (d=1.03, 95%CI=0.20, 1.85), anxiety (d=0.57, 95%CI=0.02, 1.12), and stress (d=1.13, 95%CI=0.21, 2.04) scores but no significant differences in physical activity across three-time points. On average, participants who met the physical activity guidelines had lower depression (d=-2.08, 95%CI=-2.90, -1.26), anxiety (d=-0.88, 95%CI=-1.41, -0.34), and stress (d=-1.35, 95%CI=-2.13, -0.56) scores compared to those not meeting the guidelines. Conclusions: In the context of the ongoing COVID-19 pandemic, both governments and service providers should continue to provide the public with timely mental health support and promote the benefits of physical activity, as a cost-effective strategy to improve mental health and wellbeing.